De l´'localisme a la universalitat via Protocol i maridatge de conceptes soci-religiosos: Corpus Christi, Berga i la Patum - Lafuente, Carlos Fuente (Journal of the sociology and theory of religion, 2017)
The protocol (at Corpus Christi, Berga and La Patum), it is the instrument that interacts, binds and amalgamates the form and base, structure and content, the concrete and abstract being, matter and spirit, and the soul of those here with those on the afterlife. It is the tool that gives roots and significance in Heaven, on Earth and the tradition that men and women have been able to create, grow and conclude over time. And this fidelity and this loyalty to its essence, in its timeless creed and temporal beliefs are what make people live with conviction, determination, enthusiasm, emotion and hope and, at the same time, conferring geographic and temporal projection, so what they do can interest and can agree to all people under the sun, beyond the particular circumstances of the community.